Estimation of Electrical Power Needs at PT PLN UP3 Luwuk Using The Linear Regression Method - Budianto, Budianto; Mohamad, Yasin; Wiranto, Ifan; Matoka, Arifin; Tolago, Ade Irawaty; Amali, Lanto Mohamad Kamil (Jambura Journal of Electrical and Electronics Engineering, 2025)
Banggai Regency is one of the areas in Central Sulawesi experiencing rapid economic growth. This condition has led to an increased demand for electricity in the region. Therefore, accurate predictions of electricity demand are needed for proper planning in providing electricity in the future. This research aims to predict the electricity demand in Banggai Regency for the next three years (2024-2026). The research employs the Simple Linear Regression method using historical data on electricity consumption in Banggai Regency. The prediction results indicate that the electricity demand in Banggai Regency will continue to increase. The increase in customers is noted with a percentage increase in social (13,956%), households (12,222%), businesses (8,289%), industries (40,752%), and government (8,014%). The increase in connected power is recorded with a percentage increase in social (30,502%), households (18,315%), businesses (16,037%), industries (40,373%), and government (6,704%). This information is crucial for stakeholders to plan adequate and sustainable electricity infrastructure and policies in Banggai Regency in the future.Kabupaten Banggai merupakan salah satu daerah di Sulawesi Tengah yang mengalami pertumbuhan ekonomi yang cukup pesat. Hal ini menyebabkan peningkatan kebutuhan energi listrik di daerah tersebut. Untuk itu, diperlukan prediksi kebutuhan energi listrik yang akurat agar dapat dilakukan perencanaan yang tepat dalam penyediaan energi listrik di masa depan. Penelitian ini bertujuan untuk memprediksi kebutuhan energi listrik di Kabupaten Banggai dalam kurun waktu tiga tahun ke depan (2024-2026). Metode yang digunakan dalam penelitian ini adalah metode regresi linier sederhana dengan menggunakan data historis konsumsi energi listrik di Kabupaten Banggai. Hasil prediksi menunjukkan bahwa kebutuhan energi listrik di Kabupaten Banggai akan terus meningkat di masa depan Kenaikan pelanggan didapatkan kenaikan dengan persentase sebesar: sosial (13,956%); rumah tangga (12,222%); bisnis (8,289%); industri (40,752%); dan pemerintah (8,014%). Peningkatan daya tersambung tercatat dengan peningkatan persentase sebesar: sosial (30,502%); rumah tangga (18,315%); bisnis (16,037%); industri (40,373%); dan pemerintah (6,704%). Informasi ini penting bagi pemangku kepentingan terkait untuk merencanakan infrastruktur dan kebijakan kelistrikan yang memadai dan berkelanjutan di Kabupaten Banggai di masa depan.